Aplicação dos efeitos prospectivos à decisão judicial que altera entendimento consolidado e reconhece uma relação jurídica tributária - Marinho, Rodrigo César de Oliveira (2015)
This work is a study regarding the limitation of the effects and particularly of the prospective effects of decisions issued by appellate courts that result in a change to a previous holding and, consequently, recognize a new or more burdensome legal tax relationship. It begins with the distinction between a legal rule and the text of the law (prescriptive statement), with the legal rule being considered to be the result of an interpretive process conducted by all those who have the necessary cognitive ability. For them, the judicial branch is the authentic interpreter the one with the last word regarding what the law is, regardless of and overriding other interpretive results. When the interpretive results are coincident (the same legal rule) or when the judicial branch states the meaning of the legal rule, there is an idealization of a stable nucleus of legal rules. That nucleus represents certainty in regard to the meaning that should be attributed to a given normative text, so as to produce foreseeability and stability, founded on a general state of legitimate expectations and acting as guidelines for taxpayers conduct. Working from these premises, on the basis of legal certainty, which is a fundamental element of a democratic state that intends to be subject to the rule of law, set upon the pillars of the principals of private property, liberty and equality and grounded on the application of the rules of non-retroactive enforcement and legality to legal rules (and not merely to legal texts), this work seeks to justify the necessary prospective limitation of the effects of a decision that establishes a new legal holding, which consequently eliminates a previously settled holding, in relation to which taxpayers acted based on the legitimate expectation that they were acting in accordance with that which the authentic interpreter of the law held to be correct